PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SD NEGERI 3 TALANG MANDI - Ismayenti Ismayenti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is motivated by the results of students' mathematics learning is still low. This study was conducted on studentsof class I of SD Negeri 3 Talang Mandai. This study aims to improve student mathematics learning outcomes throughrealistic mathematic education (RME). From the analysis of data from observations of teacher activity activities, in cycle Iobtained a percentage value of 62.5 in the poor category, at the second meeting increased to 79.16 with sufficient categories,meeting three gained a percentage value of 87.5 in the good category, while meeting four increased to 95.83 in the categoryvery good. In terms of student activity, in cycle I, the percentage score was 58.33 in the less category, at the second meetingit increased to 70.83 with enough categories, the meeting of three cycles II, obtained a percentage value of 79.16 withenough categories, while the fourth meeting increased to 91.66 with very good category. For student learning outcomes, thebasic score, the average value of 56.5 class with less category. in the first cycle the average value of 65.5 class with enoughcategories. Cycle II, the average value of 90.5 grade with very good pesentase. From the data analysis, it can be concludedthat the realistic mathematic education (RME) which is applied to the learning process is very effective, this is evidenced bythe increase in student learning outcomes in class I of the SD Negeri 3 Talang Mandai.